Calidad fisicoquímica de Proparacaína Clorhidrato 0,5% solución oftálmica, 2018 - Adrianzen Tolentino, Mario Andres (2018)
The present report of pre-professional practices was aims to evaluate the physicochemical quality of Proparacaine Hydrochloride 0.5% ophthalmic solution, which has the active ingredient Proparacaine Hydrochloride. The tests were carried out in the Laboratory of the Quality Control Area of the Pharmaceutical Industry. The representative sample of the product consisted of 60 dropper bottles from Batch 102108. The physicochemical tests evaluated were: Description, average volume, pH, identification, titration, particle count and preservative content; according to the Official Monograph of the Pharmacopoeia of the United States (USP) 40 and the Analytical Technique of Finished Product. The product was described as a colorless solution, free of visible particles; its average volume was 15.3 mL; presented a pH of 5.23; in the identification the presence of Proparacaine Hydrochloride was determined by visualizing a red scarlet precipitate that did not dissolve when interacting with acetone; in the titration by HPLC, 5.20 mg/mL =̃ 104.0% Proparacaine Hydrochloride was obtained; in the counting of particles, 2 were obtained in diameter > 10 μm, 0 of > 25 μm and 0 of > 50 μm; in the content of preservative 0.0862 mg/mL =̃ 86.2% was obtained Benzalkonium Chloride. The results obtained were in accordance, so it was concluded that the product Proparacaine Hydrochloride 0.5% ophthalmic solution meets the specifications according to the United States Pharmacopeia (USP) 40 and the Analytical Technique of Finished Product